2022
DOI: 10.21106/ijma.557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Occupational Exposure to HIV and Factors Associated with Compliance with Post-Exposure Prophylaxis Among Health Workers of the Biyem-Assi, Buea, and Limbe Health Districts of Cameroon Maternal and Child Health and AIDS

Abstract: Background: Although a few studies have assessed occupational exposure and knowledge on post-exposure prophylaxis (PEP) for HIV among health care workers (HCWs), limited information is available on the factors that influence the use of HIV PEP among HCWs after occupational exposure in Cameroon. This study aimed to assess the prevalence and determinants of occupational exposure to HIV infection and identify factors (knowledge, attitudes, and practices) that influence compliance to the use of HIV PEP among HCWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(36 reference statements)
3
4
1
Order By: Relevance
“…This means that despite the fact that various technologies and prevention methods have been developed, HCWs are still at risk of contracting HIV in their workplaces. This is comparable with the study that was reported from South Africa (4%), 20 Tanzania (3%), 21 and Nigeria (4.2%). 22 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This means that despite the fact that various technologies and prevention methods have been developed, HCWs are still at risk of contracting HIV in their workplaces. This is comparable with the study that was reported from South Africa (4%), 20 Tanzania (3%), 21 and Nigeria (4.2%). 22 …”
Section: Discussionsupporting
confidence: 91%
“…This means that despite the fact that various technologies and prevention methods have been developed, HCWs are still at risk of contracting HIV in their workplaces. This is comparable with the study that was reported from South Africa (4%), 20 Tanzania (3%), 21 and Nigeria (4.2%). 22 However, the result is much higher than the studies conducted in Iran (1.7%), 23 Australia (2.1%), 24 Kenya (1.5%), 25 and Tunisia (1.7%).…”
Section: Discussionsupporting
confidence: 91%
“…The findings from this study shows that 27.3% had previous exposure to Occupational HIV which is lower compared to the submission of (Eyong et al, 2022) who reported over half of the health care workers (63.5%) had suffered occupational injuries.…”
Section: Discussioncontrasting
confidence: 66%
“…whereas Cameroon exhibited a range from 36.7% to 63.5% [25][26]. Egypt disclosed a notably high prevalence of 83.3% [27].…”
Section: Prevalence Of Peis In Africamentioning
confidence: 94%
“…The reviewed articles revealed statistically significant relationships between the occurrence of PEIs and various factors. These factors include age [25,47,54,57,72], type of healthcare facilities [25,30], gender [27,28,32,39,43,45,48,57,72], occupation [10, 27, 34, 35, 41-43, 46, 54, 57, 67], work experience [27,30,31,36,54,58,72], needle recapping [27,29,33,37,39,40,42,44,45,60], increased workload [27,29], not observing universal precautions and using personal protective equipment (PPE) [27,29,37,40], remuneration [35], hand hygiene practices [30,35],…”
Section: Predictors Of Peis In Africamentioning
confidence: 99%